A Study on NGO Services for Children in Mumbai, India - Reeta Sonawat; Shanna Sikh (Jurnal ILMU KOMUNIKASI, 2007)
Abstract: The present research was conducted to study NGOs services for children in Mumbai through a child rights perspective. The study was exploratory in nature and aimed to assess the implementation of child rights by the NGOs. 35 NGOs working for children in the city of Mumbai comprised the sample and were studied using a questionnaire and rating scale as tools. Findings revealed that education (74 percent) and health (54 percent) were the most common concerns of the organizations. Only 17 percent of the NGOs considered child rights to be a concern. The NGOs implemented the right to participation better than any other right. The right to survival was, however, grossly neglected. It was concluded that there are several gaps and areas of lack in the services offered to children. There is also an urgent need to spread awareness amongst the NGO workers themselves to make child rights a part of organizational mandates.